ORGANIZING AND CONDUCTING WRESTLING COMPETITIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article describes in detail the rules for organizing and holding a wrestling competition. In addition, the rules of the organization of the competition, the composition of the judges, their duties, criteria for evaluating the competition, hygienic rules of the competition were discussed.